The effect of anesthetic preconditioning with sevoflurane on intracellular signal-transduction pathways and apoptosis, in a lung autotransplant experimental model - Garutti,Ignacio (2019)
Abstract Background: Anesthetic pre-conditioning attenuates inflammatory response during ischemia-reperfusion lung injury. The molecular mechanisms to explain it are not fully understood. The aim of our investigation was to analyze the molecular mechanism that explain the anti-inflammatory effects of anesthetic pre-conditioning with sevoflurane focusing on its effects on MAPKs (mitogen-activated protein kinases), NF-κB (nuclear factor kappa beta) pathways, and apoptosis in an experimental lung autotransplant model. Methods: Twenty large white pigs undergoing pneumonectomy plus lung autotransplant were divided into two 10-member groups on the basis of the anesthetic received (propofol or sevoflurane). Anesthetic pre-conditioning group received sevoflurane 3% after anesthesia induction and it stopped when one-lung ventilation get started. Control group did not receive sevoflurane in any moment during the whole study period. Intracellular signal-transduction pathways (MAPK family), transcription factor (NF-κB), and apoptosis (caspases 3 and 9) were analyzed during experiment. Results: Pigs that received anesthetic pre-conditioning with sevoflurane have shown significant lower values of MAPK-p38, MAPK-P-p38, JNK (c-Jun N-terminal kinases), NF-κB p50 intranuclear, and caspases (p < 0.05) than pigs anesthetized with intravenous propofol. Conclusions: Lung protection of anesthetic pre-conditioning with sevoflurane during experimental lung autotransplant is, at least, partially associated with MAPKs and NF κB pathways attenuation, and antiapoptotic effects.